Request to return exceeding retention deduction till running bill no. 009 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding request to return exceeding retention deduction till running bill no. 009 of BRAC University new campus project.